2015
DOI: 10.1177/1090198114566453
|View full text |Cite
|
Sign up to set email alerts
|

African Americans’ Perceptions of Prostate-Specific Antigen Prostate Cancer Screening

Abstract: Background In 2012, the US Preventive Services Task Force (USPSTF) released a hotly-debated recommendation against prostate-specific antigen (PSA) testing for all men. The present research examines African Americans’ beliefs about their susceptibility to prostate cancer (PCa) and the effectiveness of PSA testing in the context of the controversy surrounding this recommendation. Methods This study used a qualitative design to examine perceptions regarding susceptibility along with screening and facilitators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 14 publications
3
42
0
Order By: Relevance
“…Along with purposive sampling, Jones and colleagues also used “snowball” sampling. Four studies recruited participants from medical centers, 5 studies recruited participants from the community, and 1 study recruited participants from both community and medical sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with purposive sampling, Jones and colleagues also used “snowball” sampling. Four studies recruited participants from medical centers, 5 studies recruited participants from the community, and 1 study recruited participants from both community and medical sites.…”
Section: Resultsmentioning
confidence: 99%
“…Sample size in studies ranged from 14 to 81 participants. Most studies obtained data directly from participants through semistructured interviews or focus group discussions . Owens and colleagues included additional survey data collected prior to and following education sessions.…”
Section: Resultsmentioning
confidence: 99%
“…The SCT and ALT were used throughout the process. Recognizing the role of women was an important contribution to the curriculum since they are viewed as key conduits for getting information to their husbands and other family members [15]. Further, the team provided the ambassadors with a multimodal toolkit containing teaching tools that are appropriate for different types of presentations: a wallet card for one-on-one conversations, a table-top flip chart for small group discussions, and a set of slides for larger presentations.…”
Section: Discussionmentioning
confidence: 99%
“…For one, the curriculum acknowledged the role of women in helping their loved ones make decisions about prostate health by making the training material inclusive along with the provision of practical skills training for being a female ambassador. This addition followed a lesson learned from formative work, in which focus group participants identified women as important vehicles for helping convince the men in their lives to go to the doctor and care for their health [15]. The curriculum trained individuals to identify the limitations of PSA screening and then provided them with guidance for speaking with others in their community about the informed decision-making process without pressuring those community members to make a specific or predefined choice.…”
Section: Enhancing the “On The Ground” Curriculummentioning
confidence: 99%
“…[77–80] Two survey studies showed that there was awareness on the screening controversy yet the majority of men still believed that screening saved lives and should be used despite the USPSTF recommendation. [81, 82] Jemal et al examined the recent changes in stage specific incidence and PSA testing rates. The authors used SEER data on invasive PC incidence data from 2005 to 2012 and had the availability of 2013 incidence data from one registry (Georgia).…”
Section: Methodsmentioning
confidence: 99%